PLATINUM China: A prospective, randomized investigation of the platinum chromium everolimus‐eluting stent in de novo coronary artery lesions. Issue 1 (18th February 2015) - Gao, Runlin; Han, Yaling; Yang, Yuejin; Zhang, Jian; Hou, Yuqing; Wang, Haichang; Li, Hui; Fang, Quan; Yu, Bo; Xu, Bo; Allocco, Dominic J.; Dawkins, Keith D.
<x xml:space="preserve">Abstract</x> Objectives The PLATINUM China clinical trial evaluated the safety and effectiveness of the thin‐strut, everolimus‐eluting, platinum‐chromium PROMUS™ Element™ stent (PtCr‐EES) (Boston Scientific, Marlborough, MA) for the treatment of patients in China. Background Clinical outcomes from the PtCr‐EES have not been evaluated in patients from China, nor has it been directly compared with the second‐generation stainless steel paclitaxel‐eluting TAXUS Liberté stent (PES) in a randomized head‐to‐head trial. Methods In this prospective, multicenter, single‐blind, superiority trial, patients with a single de novo atherosclerotic coronary artery lesion were randomized 1:3 to receive either the PES or PtCr‐EES. The primary endpoint was in‐stent late loss at 9 months. Results Among 127 PES and 373 PtCr‐EES patients (71.2% male; mean age 57.3 years), the primary endpoint of 9‐month in‐stent late loss was 0.40 ± 0.45mm for PES versus 0.11 ± 0.36 mm for PtCr‐EES (P < 0.001). In‐stent % diameter stenosis was 22.20±16.00% for PES versus 11.06±13.86% for PtCr‐EES (P<0.001) at 9 months. The 1‐year rate of death/MI was 1.6% (2/127) for PES versus 0% (0/371) for PtCr‐EES (P=0.06) and target vessel revascularization was 4.7% (6/127) for PES versus 2.7% (10/371) for PtCr‐EES (P=0.26). No stent thromboses occurred at12 months in either group. Conclusions In the largest prospective angiographic evaluation conducted to date with this stent, the PROMUS Element PtCr‐EES was superior to the TAXUS Liberté PES for the primary endpoint of late loss at 9 months, with low rates of clinical events at 1 year. Clinical follow‐up will continue to 2 years. © 2015 Wiley Periodicals, Inc.